Micropropagation of mature cork-oak (Querqus suber L.): establishment problems - Romano, A; Martins-Loução, M a (Scientia gerundensis, 1992)
Procedures have been developed to standardize the establishment stage during mature cork-oak (Quercus suber L.) micropropagation. Axillary and terminal buds cultured in Gresshof and Doy (1972) (GD) medium were used as first explant. Establishment of cultures was very difficult due to browning of the tissue and/or the medium and bacterial contamination. Browning problems, probably due to phenolic compounds exudation of the primary explant, were found to be higher in winter. Nevertheless, initiation of cultures was possible all over the year, presumably due to the preconditioning of cuttings. Explants were established in a GD medium containing 6-benzlaminopurine (BAP) 1 mgl-1. Every 4 weeks the cultures were subcultured to the same GD medium and induced to proliferate being 4:1 the multiplication rate. Shoots were induced to elongate by decreasing BAP concentration. In vitro rooting on agar-solidified medium suplemented with 1 mgl-1 indolacetic acid (IAA) gave the best results. Liquid medium (sorbarod system) and in vivo rooting were also assayed.
Keywords: browning; contaminants; cork-oak; micropropagation; phenolic compounds; Quercus suber L.; tissue culture